Pengaruh Kualitas Pelayanan, Harga, Dan Promosi Terhadap Keputusan Pelanggan Dalam Menggunakan Jasa Pengiriman - Ferdinand Setiawan Djaja; Bruno Hami Pahar (BIP's JURNAL BISNIS PERSPEKTIF, 2020)
The number of delivery service providers in Indonesia has grown to be very large, so that consumers have many choices. Consumers must be able to choosecarefully and smartly for the delivery services to use. The rapid development of ecommerce has affected the business of providing goods delivery services inIndonesia. E-commerce causes delivery service providers to have a new strategy, so as not to lose in competition in the shipping service business. One of thedelivery service providers is J&T Express. This study aims to determine the effect of Service Quality (X1), Price (X2), and Promotion (X3) on Customer Decision(Y) to use delivery services at J&T Express Kedung Cowek, Surabaya. The population in this study were customers or consumers at J&T Express KedungCowek, Surabaya. The results showed that promotion had a significant effect on service use decisions, while Service Quality and Price had no effect on thedecision to use delivery services at J&T Express Kedung Cowek, Surabaya.